2015
DOI: 10.1109/tkde.2015.2411278
|View full text |Cite
|
Sign up to set email alerts
|

Non-Myopic Adaptive Route Planning in Uncertain Congestion Environments

Abstract: We consider the problem of adaptively routing a fleet of cooperative vehicles within a road network in the presence of uncertain and dynamic congestion conditions. To tackle this problem, we first propose a Gaussian Process Dynamic Congestion Model that can effectively characterize both the dynamics and the uncertainty of congestion conditions. Our model is efficient and thus facilitates real-time adaptive routing in the face of uncertainty. Using this congestion model, we develop efficient algorithms for nonm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In [33], the authors proposed pCruise system to reduce the taxi's cruising miles by providing the shortest cruising route with at least one expected available passengers for this route. In [34], the authors developed efficient algorithms for non-myopic adaptive routing to minimize the collective travel time of all vehicles in the system. In [35], the authors proposed solutions to reduce the number of cruising miles while increasing the number of live miles of taxis by suggesting profitable locations to taxicab drivers.…”
Section: Related Workmentioning
confidence: 99%
“…In [33], the authors proposed pCruise system to reduce the taxi's cruising miles by providing the shortest cruising route with at least one expected available passengers for this route. In [34], the authors developed efficient algorithms for non-myopic adaptive routing to minimize the collective travel time of all vehicles in the system. In [35], the authors proposed solutions to reduce the number of cruising miles while increasing the number of live miles of taxis by suggesting profitable locations to taxicab drivers.…”
Section: Related Workmentioning
confidence: 99%
“…Of particular importance in adaptive sampling methods is the choice of the acquisition function for evaluating candidate sample locations. Common approaches for this optimization criteria are based on entropy (Low et al, 2009), mutual information (Krause et al, 2008), or the combination of the predictive mean and information gain (Liu et al, 2015). Additionally, the work in Cao et al (2013) compares the effectiveness of entropy and mutual information criteria.…”
Section: Related Workmentioning
confidence: 99%
“…Also, refueling is not considered for ICE taxis, because ICE taxi drivers normally fill up the gas tanks between the shifts 6 . Then the MDP model for an ICE taxi is identical to that of an electric taxi in Sec.…”
Section: A Basic Setting Of Ice Taximentioning
confidence: 99%
“…They also found that better taxi drivers can deliver the passengers efficiently by choosing a uncongested route. Furthermore, GPS mobility trace from taxis can be used to predict future traffic conditions and optimize the route selections [6]. Also, community detection has been applied to the mobility trace to reveal potential similar passengers' travel patterns, as for social recommendation [7] and improving transportation services [8].…”
Section: Background a Related Workmentioning
confidence: 99%
See 1 more Smart Citation